Promoting positive body image and intuitive eating in women with overweight and obesity via an online intervention: Results from a pilot feasibility study. (August 2019) - Beintner, Ina; Emmerich, Olivia Lucia Marie; Vollert, Bianka; Taylor, C. Barr; Jacobi, Corinna
Abstract: Background: Body dissatisfaction and dietary restraint are established risk factors for eating disorders and are also prevalent in individuals who are overweight and obese. Studies have shown that online prevention programs can lower these risk factors. The aim of this feasibility pilot study was to estimate effects of a 12-week online health promotion and eating disorder prevention program in a sample of women with overweight or obesity, but without binge eating. Methods: The program was evaluated in an uncontrolled pre-post-follow-upstudy over 12 months. Outcome measures were eating disorder related cognitions and attitudes. Participants were recruited via flyers, online posts, press releases, and mailings through cooperating health insurances. Results: 371 women who completed the screening met the inclusion criteria. 323 women took part in the baseline assessment and were granted access to the intervention. 50 women completed all sessions. An intention-to-treat analysis showed significant and long-term reductions in weight and shape concerns, restrictive eating and increases in life satisfaction and self-esteem (d = 0.31–0.86), and a short-term increase in fruit and vegetable consumption (d = 0.70). Conclusion: everyBody fit seems a feasible program for improving body image and reducing disordered eating in overweight and obese women, with medium to large effects on various outcomes. The efficacy of the intervention needs to be established in a randomized controlled trial. Highlights: Dietary restraint and body dissatisfaction are common in women with high weight. We developed an online eating disorder prevention program for these women. We evaluated the feasibility the program in an uncontrolled pilot study. Dietary restraint and body dissatisfaction could be reduced. Improvements were maintained at 12-month follow-up.